Transmission network investment across national borders: The liberalized electricity market - Lars Persson; Thomas P. Tangerås (Research Institute of Industrial Economics (IFN), 2018)
The world's first multinational electricity market was formed with the creation of the Nordic power exchange, Nord Pool. We analyze the incentives to undertake transmission network investment in the context of the liberalized Nordic electricity market. Welfare improving investment in a multinational electricity market requires accounting for the cross-border effects of capacity expansion. We propose methods to increase voluntary cooperation on international infrastructure projects, with an aim to increase aggregate efficiency and achieve equitable distribution of the gains from market integration.
Keywords: C71; F15; L43; L94; 330; Coalition formation; Cross-border transmission investment; Multilateral bargaining; Nordic electricity market; Shapley Value